Vibration analysis of a vehicle system supported on a damper-controlled variable-spring-stiffness suspension - Ghosh M.K.; Dinavahi R. (My University, 2025)
Vibration isolation performance has been investigated for a vehicle system supported on a damper-controlled variable-spring-stiffness suspension system. A half-car model has been analysed for different values of damping ratio, relative damping ratio, and mass ratio. The semi-active control of a half-car model has been investigated with the help of a force generator as well as with optimal control theory. The results show that a damper-controlled variable-stiffness suspension improves the vibration isolation performance of the suspension system. It has been found that a lower damping ratio, a relative damping ratio of unity, and a higher mass ratio gives optimum reduction in the transmissibility of motion from road surface to the vehicle body. The semi-active control of a half-car model supported on a damper-controlled variable-spring-stiffness suspension can be achieved using a force generator or an actuator. The use of a force generator can minimize the power required to control the damper. A full-state feedback and linear quadratic regulator control theory gives better results for higher mass ratios. © IMechE 2005.